Politics of Study : Occasional Table - Meineche Hansen, Sidsel; Vandeputte, Tom (London ; Odense : Open Editions : Funen Art Academy, 2015)
With contributions by Andrea Fraser, Brian Holmes, Gal Kirn, Gerald Raunig, Judy Chicago, Melissa Gordon Marina Vishmidt, Ruth Sonderegger, Suhail Malik, Timothy Ivison and The New Centre for Research Practice.
Universities and art schools alike have been subjected to the pressure of recent austerity politics and the ongoing attempt to transform higher education on the basis of neoliberal principles. In this context, there is an urgent need to conceive of alternative frameworks and methodologies of study--whether this is within, outside or at the margins of academic institutions. This book examines what is currently at stake in education through a series of conversations with artists, theorists, activists and educators who are all actively involved in developing new models of study. Ranging from self-organized learning to critical teaching methodologies, the conversations gathered here offer a resource for those interested in the renewed politicization of education and alternative modes of pedagogy and inquiry. (provided by publisher)
boek